The critical commitment of philosophy. On Marcuse’s critical project - Mauricio García Echeverri (Revista Ciencias y Humanidades)
The present essay is not intended to be something new about Herbert Marcuse. As a personal exercise to clarify concepts, its aim is to provide an overview of Marcuse’s conception, based especially from his book One-Dimensional Man, about an advanced industrial society and how our thinking is being more and more rooted in what social elites want us to believe. At the same time, the article provides a basis to think this problem in an increasing postmodern society that is forgetting the most important critical authors of the 20th century and its main preoccupation: the identity between subject and society.